Insectes des Bâtiments d’élevages avicoles des fermes de Bingerville, Côte d’Ivoire : Alphitobius diaperinus (Panzer, 1797) (Coleoptera: Tenebrionidae) - Félicia, Johnson; Adolphe, Gbon Gueu; Pierre, Boga Jean (European Scientific Journal, ESJ, 2018)
This study was conducted in two sides of Bingerville (Abatta and Anna) in southern Côte d’Ivoire. The objective was to inventory the entomofauna of poultry farms in order to verify the presence of Alphitobius diaperinus (Coleoptera: Tenebionidae) in Côte d’Ivoire. It also aimed to establish correlation between Alphitobius diaperinus density in livestock buildings and the loss on poultry production. Thirty (30) poultry buildings were investigated during 3 months. A survey questionnaire on farm characteristics, diseases and mortality was submitted to farmers. The poultry litter was collected, transported to the laboratory and excavated. Insects were determined and counted. A total of 19661 insects were collected on both sites. Alphitobius diaperinus accounts for 96.63% of collected insects. The statistical comparison showed that A. diaperinus is the most representative insect (P <0.0001). This insect is unevenly distributed in chicken farms (n = 89, F = 3.67, and P ˂ 0.00001). Out of 18998 Alphitobius diaperinus collected, a total of 14362 (75.60%) were recorded in the column of feeders and waterers, and only, 4636 (24.40%) off feeders and waterers’. The study also revealed a strong correlation (R = +0.88) between the density of A diaperinus and the loss on chicken production due to avian diseases such as Gumboro, Newcastle, and Mareck. This insect is suspected to be the vector of these aggressive diseases of poultry. Our results reveal for the first time, the effective presence of Alphitobius diaperinus in poultry farms in Côte d’Ivoire.